Community-based tourism in the developing world community learning, development and enterprise - Wiltshier, Peter; Clarke, Alan 1956- (Abingdon, Oxon New York, NY Routledge, 2020)
"This book analyses community-based approaches to developing and regenerating tourism destinations in the developing world, addressing this central issue in sustainable tourism practices. It reviews a variety of systems useful for analysing and understanding management issues to offer new insight into the skills and resources that are needed for implementation, ongoing monitoring and review of community-based tourism. Adopting a multidisciplinary approach, this book explores alternatives to the dominant interpretation which argues against tourism as a benefit for community development. International case studies throughout the book illustrate and vouch for tourism as a transformative force while clarifying the need to manage expectations in sustainable tourism for community development, rejuvenation and regeneration. Emphasis is placed on accruing relevant decision-support material, and creating services, products and management approaches that will endure and adapt as change necessitates. This will be of great interest to upper-level students, researchers and academics in the fields of tourism impacts, sustainability, ethics and development as well as the broader field of Geography"-- Provided by publisher.
Includes bibliographical references and index.
Peter Wiltshier has a PhD which explored responsible development of tourism in a creative and dedicated fashion; creatively supporting communities to provide resources for their welfare and dedicated to the pursuit of a responsible future with a focus on the beautiful and important 'Green Lungs' of rural Britain in the East Midlands and in New Zealand. His role as senior lecturer destination and community tourism management at the University of Derby Buxton is to ensure that the public and private sector work together to develop resources and skills for communities to take charge of their own destinies. He also works with the Diocese of Derby to identify how tourism can benefit churches. He supports the county, the district and parishes within Derbyshire and the Peak District in their endeavors to create a better environment for all through purposeful leisure and recreation. Alan Clarke, is employed at the University of Pannonia in Hungary, where he has been appointed as a full Hungarian professor. His commitment to communities has been marked throughout his career, beginning with his teaching in community education in Sheffield, followed by time with the community education team at the Open University. He has led research in the inner city of Salford and worked with the Roma community in the North West of England. He has been known to say that the best chapter in his PhD was the one on community development (which never appeared). The Derby Jubilee Community Festival crystalised a number of issues - power, hegemony, inclusion, engagement and capacity building - plus the opportunity to develop a lifelong friendship with Allan Jepson. Alan moved to Hungary where communities and festivals are constructed differently. There were hard lessons in coming to terms with this - cultures, structures and stakeholder relations have to be seen through differently sensitised lenses. This opened up an interest with religious and heritage tourism and the ways these belief systems impacted on the cultures in which they are experienced in the communities that give them life. It was here that he made the significant bond with his co-editor, Peter Wiltshier.
Keywords: Sustainable tourism -- Developing countries; Community development -- Developing countries; Tourism -- Social aspects -- Developing countries; Tourism -- Developing countries